Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fimmu.2022.989000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological ascorbate as a novel therapeutic strategy to enhance cancer immunotherapy

Abstract: Pharmacological ascorbate (i.e., intravenous infusions of vitamin C reaching ~ 20 mM in plasma) is under active investigation as an adjuvant to standard of care anti-cancer treatments due to its dual redox roles as an antioxidant in normal tissues and as a prooxidant in malignant tissues. Immune checkpoint inhibitors (ICIs) are highly promising therapies for many cancer patients but face several challenges including low response rates, primary or acquired resistance, and toxicity. Ascorbate modulates both inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“… 108–111 Evaluating vitamins as treatment adjuncts for ICB bases on rational assumptions (many vitamins are immune modulators) and is also supported by a wealth of quite promising early-stage data. 112–116 An important study recently found an association of vitamin E intake with improved survival of ICB-treated patients, with vitamin E enhancing anticancer immunity by targeting the DC-intrinsic immune checkpoint SHP1 and fostering cross-presentation of tumor antigens to up immune surveillance. 117 Similarly, a study involving 200 patients with advanced melanoma treated with PD-1 inhibitors (nivolumab or pembrolizumab) showed that vitamin D supplementation increased the objective response rate and significantly prolonged progression-free survival (PFS).…”
Section: Vitamins and Nutraceuticalsmentioning
confidence: 99%
“… 108–111 Evaluating vitamins as treatment adjuncts for ICB bases on rational assumptions (many vitamins are immune modulators) and is also supported by a wealth of quite promising early-stage data. 112–116 An important study recently found an association of vitamin E intake with improved survival of ICB-treated patients, with vitamin E enhancing anticancer immunity by targeting the DC-intrinsic immune checkpoint SHP1 and fostering cross-presentation of tumor antigens to up immune surveillance. 117 Similarly, a study involving 200 patients with advanced melanoma treated with PD-1 inhibitors (nivolumab or pembrolizumab) showed that vitamin D supplementation increased the objective response rate and significantly prolonged progression-free survival (PFS).…”
Section: Vitamins and Nutraceuticalsmentioning
confidence: 99%
“…Vit C enhances the cytotoxic activity of Tils in CAR-T therapy and cooperates with ICIs therapy. This has provided a rationale for clinical trials combining ICIs with high doses of Vit C, as this antioxidant protection treatment can convert ROS into less reactive species [33][34][35].…”
Section: Ros In Cancer Immunotherapymentioning
confidence: 99%
“…Interestingly, the potential pro-oxidant role of pharmacological doses of Vit C has been successfully harnessed as a radio-sensitizer and a chemo-sensitizer in preclinical studies and early-phase clinical trials. This has suggested that it may also increase both the efficacy and benefits of ICIs [33,34]. Furthermore, Vit C affects multiple immune cell functions and can help overcome resistance to ICIs due to cytotoxic T-lymphocyte antigen 4 (CLTA-4) and programmed cell death ligand 1 (PD-L1/PD-1) inhibitors.…”
Section: Ros-based Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, pharmacological ascorbate (high-dose intravenous infusions of vitamin C resulting in plasma concentrations of ≈20 mM, P-AscH − ) has garnered attention as a potential anticancer agent to enhance the response to SOC therapy across various malignancies, including GBM [12][13][14][15][16]. When ascorbate is oxidized, it generates high levels of hydrogen peroxide (H 2 O 2 ), which can react with redox-active iron, primarily Fe 2+ , through Fenton chemistry, resulting in an excess of damaging hydroxyl radicals capable of disrupting biological macromolecules [12,13,16,17].…”
Section: Introductionmentioning
confidence: 99%